2009
DOI: 10.1200/jco.2008.18.7252
|View full text |Cite
|
Sign up to set email alerts
|

Bendamustine: Rebirth of an Old Drug

Abstract: Bendamustine is a unique cytotoxic agent with structural similarities to alkylating agents and antimetabolites, but which is non-cross-resistant with alkylating agents and other drugs in vitro and in the clinic. Early clinical studies conducted in the German Democratic Republic more than 30 years ago suggested promising activity in indolent non-Hodgkin's lymphoma (NHL). Two North American trials reported responses in more than 70% of patients with chemotherapy- and rituximab-refractory disease, suggesting that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
124
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(132 citation statements)
references
References 61 publications
1
124
0
7
Order By: Relevance
“…DNA damage is more extensive and it occurs with slower and different DNA repair pathways than other alkylators. 72,73 Use in lymphoma. A phase 2 trial of bendamustine in patients with rituximab-refractory or -intolerant, -indolent, or -transformed lymphoma showed an overall response of 77%.…”
Section: New Agents Targeting Dna Synthesis Bendamustinementioning
confidence: 99%
“…DNA damage is more extensive and it occurs with slower and different DNA repair pathways than other alkylators. 72,73 Use in lymphoma. A phase 2 trial of bendamustine in patients with rituximab-refractory or -intolerant, -indolent, or -transformed lymphoma showed an overall response of 77%.…”
Section: New Agents Targeting Dna Synthesis Bendamustinementioning
confidence: 99%
“…Bendamustine is an alkylating agent that has purine analogue properties and exhibits considerable activity in indolent lymphomas and CLL [13,14]. It has been reported that bendamustine exerts a cytotoxic effect in CLL cell lines, involving both p53-dependent and p53-independent mechanisms [15].…”
Section: Introductionmentioning
confidence: 99%
“…Patients were treated in 1 of 3 cohorts based on investigator's choice and received continuous oral therapy with idelalisib. 4 The treatment groups received either rituximab (IV infusion of 375 mg/m 2 weekly for 8 doses), bendamustine (30-minute IV infusion of 90 mg/m 2 on days 1 and 2), or the combination of bendamustine and rituximab (bendamustine at 90 mg/m 2 on days 1 and 2, then rituximab at 375 mg/m 2 on day 1), and all groups received twice-daily idelalisib. Idelalisib was provided as 100-or 150-mg tablets, with 75-and 50-mg tablets available for dose reductions.…”
Section: Study Design and Treatmentsmentioning
confidence: 99%
“…1,2 Treating recurrent iNHL continues to be challenging. Current therapies commonly include anti-cluster of differentiation 20 antibodies, such as rituximab 3 (US approval in 1997) and the alkylator bendamustine 4 (US approval in 2008), which have demonstrated activity and tolerability in combination with rituximab. 5 Although initially effective for iNHL, standard chemotherapy and immunotherapy generally demonstrate decreasing efficacy with repeated administration.…”
Section: Introductionmentioning
confidence: 99%